Merokok dikalangan Siswa Sekolah Menengah Pertama Negeri 5 Raha - Muhammad Zaid Asidin (JURNAL KABANTI: Kerabat Antropologi, 2022)
This study aims to determine the behavior of smokers among students and to explain the actions of the school towards students who smoke at the State Junior High School 5 Raha. This study uses social action theory by Talcott Parsons, using an ethnographic-based qualitative descriptive approach. This shows that some students at the State Junior High School 5 Raha engage in smoking behavior, where they smoke secretly, namely in the school canteen and in damaged buildings. They smoke in their spare time, especially when the teacher is not in class and during recess. Where they smoke together with their peers while playing gadgets/smartphones. They do this to fill their spare time at school and relieve fatigue and boredom that exists in them. Therefore, the school has given an appeal to students who smoke in the form of providing education about the dangers of smoking to students and installing educational posters about smoking, not only that the school has also imposed sanctions for students who do smoking behavior. Where the sanctions are in the form of a table of 100, so if students violate school rules repeatedly, they will be given 100 points, which is expelled from school.